THE RELATIONS OF THE 4PS MARKETING MIX TO THE DECISION TO PURCHASE SKINCARE PRODUCTS AT THE TIKTOK SHOP - Anggraeni, Dinar Safa; Az Zahra, Maysitha Fitri; Al Khaliq, Barkah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
As one of the national priority industrial sectors, the cosmetics industry continues to experience growth driven by growing consumer awareness of health and beauty. The phenomenon of technological development has impacted changes in consumer behaviour in purchasing cosmetic industry products, especially online purchases made through social media, e-commerce or live broadcasts. This research aims to determine purchasing decisions regarding types of skincare products at the TikTok Shop. The population in this study were skincare consumers from Jabodetabek aged 25-35 years. The sample size was 275 respondents who filled out the questionnaire. The questionnaire's independent elements are listed in the 4Ps marketing mix (Price, Product, Promotion and Place). Meanwhile, the dependent factor measured is the purchasing decision when seeing sales of viral skincare products on the TikTok Shop. This research uses a regression method to find relationships between variables with the SmartPLS application. This research shows that promotion and price are the most significant factors influencing consumers when purchasing skincare products at the TikTok Shop.Keywords: Tiktok Shop, Cosmetics Industry, Promotions, Prices, Purchasing Decision.